2021
DOI: 10.1177/03000605211014364
|View full text |Cite
|
Sign up to set email alerts
|

Functional repair of the great saphenous vein by external valvuloplasty reduces the vein's diameter: 6-month results of a multicentre study

Abstract: Objectives External valvuloplasty (eVP) is a reconstructive surgical method to repair the function of the terminal and preterminal valves. We evaluated the 6-month outcomes of eVP regarding the diameter of the great saphenous vein (GSV). Methods Patients from five vein centres were included in this observational study. Follow-up involved detailed duplex sonography of the GSV. The venous clinical severity score (VCSS) and the C class of the clinical, aetiologic, anatomic and pathophysiologic (CEAP) classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
2
0
4
Order By: Relevance
“…Different conclusions have been reached about the degree of risk of sequential bridge occlusion (26). Pavei et al (27) followed-up with 428 patients for 15 years and found that while sequential bridges were more completely vascularized than single-vessel bridges, patients with sequential bridges also had a higher incidence of myocardial infarction and other cardiac events (28,29). We believe that sequential great SV bridges and Y-type bridges share the following common characteristics: (I) compared to single-branch bridges (point-to-point bypass bridges), SV bridges sand Y-type bridges have a larger mean blood flow, and a lower mean pulsatile index; (II) SV bridges sand Y-type bridges reduce the length of bridge vessels, reduce the operation time of anastomotic shortening, reduce the number of aortic anastomoses, which in turn can reduce the perforation and the number and time of aortic clamping, which is more meaningful for patients with more calcified plaques in the ascending aorta, and reduce postoperative arrhythmia low cardiac output and other complications.…”
Section: Discussionmentioning
confidence: 99%
“…Different conclusions have been reached about the degree of risk of sequential bridge occlusion (26). Pavei et al (27) followed-up with 428 patients for 15 years and found that while sequential bridges were more completely vascularized than single-vessel bridges, patients with sequential bridges also had a higher incidence of myocardial infarction and other cardiac events (28,29). We believe that sequential great SV bridges and Y-type bridges share the following common characteristics: (I) compared to single-branch bridges (point-to-point bypass bridges), SV bridges sand Y-type bridges have a larger mean blood flow, and a lower mean pulsatile index; (II) SV bridges sand Y-type bridges reduce the length of bridge vessels, reduce the operation time of anastomotic shortening, reduce the number of aortic anastomoses, which in turn can reduce the perforation and the number and time of aortic clamping, which is more meaningful for patients with more calcified plaques in the ascending aorta, and reduce postoperative arrhythmia low cardiac output and other complications.…”
Section: Discussionmentioning
confidence: 99%
“…In einer aktuellen Multicenterstudie ergab sich im Followup nach 6 Monaten ein signifikanter Abfall im "Venous clinical severity score" von initial 4,76 (SD: 2,13) auf 1,77 (SD: 1,57), eine signifikante Abnahme des Venendurchmessers und eine Elimination des Leistenrefluxes bei 95 % der 210 nachuntersuchten Patienten [7]. Im Gesamtkollektiv wurde in der VSM eine Thromboserate von 0,5 % ermittelt.…”
Section: Erweiterte Crossektomie Und "Laterale Crossektomie"unclassified
“…In der aktuellen Leitlinie der European Society for Vascular Surgery (ESVS) wird hingegen eine alleinige thermische Ablation der refluxiven VSAA mit einer Empfehlungsklasse von IIa und einem (niedrigen) Evidenzlevel von C aufgeführtdies auf Basis vorhandener Beobachtungsstudien [6,7]. [8,9]. Bei Anwendung der CHIVA-Technik würde die bündige Unterbrechung der VSAA an der VSM mit dem Ziel der Flussumkehr in der VSM erfolgen [10,11].…”
Section: Introductionunclassified
“…Aus der Praxis und Literatur heraus bestehen weitere Optionen bei Stammvarikose der VSM im Stadium Hach I. Hierzu zählt die extraluminale Valvuloplastie (EVP), bei welcher die VSAA im Sinne einer lateralen Crossektomie abgesetzt wird und die VSM von außen mit einer Manschette versorgt wird, um einer Dilatation und Klappeninsuffizienz vorzubeugen [8,9]. Bei Anwendung der CHIVA-Technik würde die bündige Unterbrechung der VSAA an der VSM mit dem Ziel der Flussumkehr in der VSM erfolgen [10,11].…”
Section: Introductionunclassified